A legitimacy problem. (Economist, 2018)
The article comments on the defensiveness of U.S. President Donald Trump about the effect of the Russian election-hacking effort during the 2016 presidential election. According to the author, it is impossible to know whether Russia interfered the election for Trump. The views of Senator Marco Rubio and House Speaker Paul Ryan on the relationship between the U.S. and Russia are discussed.